Analisis Kepatuhan Kunjungan Antenatalcare K4 Di Kabupaten Ogan Komering Ulu - Rizki Wulandari; Arie Wahyudi; Dewi Suryanti (Fakultas Ilmu Kesehatan Universitas Katolik Musi Charitas, 2022)
The government has a responsibility to ensure that every citizen gets quality health services in accordance with their needs, one of which is health services for pregnant women. Maternal mortality and infant mortality from a delivery process can be reduced by providing antenatal care or antenatal care services. This study aims to analyze factors related to compliance with ANC K4 visits in Ogan Komering Ulu Regency in 2021. The population in this study were all pregnant women with a gestational age of 7-9 months (Trimester 3), amounting to 637 people with a study sample amounting to 249 respondents. This research was conducted in June - July 2021. This study used a quantitative method with a cross sectional design. The statistical test used in this study was chi square and multivariate analysis using multiple logistic regression. The results showed that there was no relationship between income (p value = 0.948) and distance of residence (p value = 0.249) with the level of compliance with ANC K4 visits in OKU Regency in 202. Meanwhile, knowledge (p value = 0.000; OR = 8.654) , husband/family support (p value = 0.046; OR = 1.912) and the role of health workers (p value = 0.033; OR = 1.997) have a relationship with the level of compliance with ANC K4 visits in OKU Regency in 2021. The most dominant variable is knowledge (p=0,000;OR=8,654). Based on the results of this study, it can be used by the Health Service and Puskesmas in OKU Regency in order to increase husband's knowledge and support. To increase visit compliance, the researcher suggests to carry out activities that can increase respondents' knowledge